2019
DOI: 10.1175/jcli-d-18-0458.1
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Like Physical and Biogeochemical Ocean Response to Tropical Eruptions

Abstract: The oceanic response to recent tropical eruptions is examined in Large Ensemble (LE) experiments from two fully coupled global climate models, the Community Earth System Model (CESM) and the Geophysical Fluid Dynamics Laboratory Earth System Model (ESM2M), each forced by a distinct volcanic forcing dataset. Following the simulated eruptions of Agung, El Chichón, and Pinatubo, the ocean loses heat and gains oxygen and carbon, in general agreement with available observations. In both models, substantial global s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
45
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 80 publications
17
45
2
Order By: Relevance
“…These conditions evolve over the course of months to years and tend to be quite predictable, depending on the phase of ENSO (e.g., Zheng et al 2016). Studies have shown additional predictability of El Niño events following large volcanic eruptions due to the ocean-dynamics thermostat mechanism described by Clement et al (1996) and Eddebbar et al (2019). Sea surface temperature anomalies associated with ENSO induce patterns of organized anomalous tropical convection from which emanate global teleconnections via Rossby wave propagation, midlatitude jet alterations, and other mechanisms.…”
Section: E610mentioning
confidence: 99%
“…These conditions evolve over the course of months to years and tend to be quite predictable, depending on the phase of ENSO (e.g., Zheng et al 2016). Studies have shown additional predictability of El Niño events following large volcanic eruptions due to the ocean-dynamics thermostat mechanism described by Clement et al (1996) and Eddebbar et al (2019). Sea surface temperature anomalies associated with ENSO induce patterns of organized anomalous tropical convection from which emanate global teleconnections via Rossby wave propagation, midlatitude jet alterations, and other mechanisms.…”
Section: E610mentioning
confidence: 99%
“…The similarity in the spatial patterns of volcanically induced pH anomalies and those produced under nuclear conflict is striking (cf. Figures S5 and 2c), suggesting that volcanic forcing produces similar temperature, DIC, and thus pH anomalies (including the El Niño-like response to volcanic forcing in the eastern Equatorial Pacific, described in Eddebbar et al, 2019). However, the eruption-driven pH anomaly is both smaller (an order of magnitude) and of shorter duration (∼2 years) than in the India/Pakistan 47-Tg simulation.…”
Section: 1029/2019gl086246mentioning
confidence: 65%
“…Pinatubo eruption led to immediate increases in the flux of carbon from atmosphere to ocean and consequently, increases in the total dissolved inorganic carbon (DIC) concentration in the surface ocean. Eddebbar et al () demonstrate that air‐to‐sea CO 2 fluxes are significantly enhanced following the eruptions of Agung, El Chichón, and Pinatubo in a large ensemble of simulations with an Earth system model. Matthews et al () conduct solar radiation management climate engineering simulations with an intermediate complexity model of the coupled climate‐carbon system; they find changes in ocean pH and normalΩarag as a result of the anomalous cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The forced response to these eruptions was a substantial oceanic uptake of carbon and oxygen for the following 2-3 years (Eddebbar et al, 2019). Modern earth system models indicate that a significant negative anomaly in global sea surface temperatures (SST) was driven by the eruptions (Eddebbar et al, 2019). For the diagnostic box model, we apply the same magnitude of forced global SST cooling estimated by these models, 0.1 o C in 1982 and 0.2 o C in 1991 ( Fig S2) to evaluate the impact on ocean carbon sink variability.…”
Section: Resultsmentioning
confidence: 99%
“…S2). This estimate of the forced sea surface temperature (SST) response to the El Chichon and Mt Pinatubo volcanic eruptions is based on the Community Earth System Model Large Ensemble (CESM LENS) (Eddebbar et al, 2019). The global-mean expression of this forced temperature anomaly extends to several hundred meters depth in CESM LENS.…”
Section: Upper Ocean Box Modelmentioning
confidence: 99%